Kemanfaatan Dana Zakat Bagi Mustahik (Studi Kasus Baznas Kabupaten Lombok Timur) - Sri Nirwana Sarowati Zikri; Mu'ady Yasin; Taufik Chaidir (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2018)
This research aims to determine how the use of funds Zakat in the BAZNAS of east Lombok Timur. The method used is descriptive qualitative research with field research type (field research). Zakat is a financial obligation which is taken from the rich who have become obligatory zakat to be submitted to the people that the criteria have been specified in the law. Zakat basically has great potential to become financial solution, with the nature of zakat that never exhausted or even stop. because zakat as the religious obligation taht must be fulfilled by a Muslim every year or in the others predetermined time. Badan Amil Zakat NASIONAL (BAZNAS) as the formal management zakat institutions in Indonesia, distribute zakat fund to the zakat recipient (mustahik), especially for the indigent and poor people through consumptive zakat to but their daily basic needs, and also can be a productively zakat to gain their business assets. Just as the mustahik utilize the zakat funds for their efforts as a household can produce an economy that can meet the needs of his life. In addition, some are using the funds that have been received zakat to raise cattle and goats. Not apart from the purpose of zakat itself which one of them is to alleviate the mustahiq of poverty, Because zakat funds are not used in a consumptive manner, but secra productive that is managed and maximized so that it can prosper the community. But it is different with the mustahik in BAZNAS, they utilize zakat funds not in accordance with the designation. This is due to the lack of monitoring from BAZNAS staff.